Competitividade das destinações turísticas a longa distância: realidade e perspectivas de desenvolvimento na América do Sul - Beni, Mário Carlos (Revista Turismo em Análise, 1993)
The text discusses tourism and the capitals flow focusing on the competitivity of long distance tourist destinations, the interest of the Government in tourism promotion and the role. Within this last issue, the necessity of developing well planned air routes and infrastructure in the Southern Atlantic region is proposed, stressing the importance of integrated schedules.